Estrategias para disminuir el impacto ambiental de las aguas residuales industriales generadas en los lavaderos de carros (2017)
The following monograph was conducted an investigation regarding the car wash industry in the country, to know how they operate, what are the most used materials and supplies. Then we proceeded to determine in which stages the water resource is more committed, recognizing its major pollutants. On the other hand, a digital search was done at a global level to have an approximation of the water consumption of a laundry room, likewise a car wash was contacted that operates in the city of Bogotá, which very generously shared some files where they found data of characterization of vertimientos, consumption of waters through their receipts of collection on the part of the Company of Aqueduct and Sewer system of Bogotá (EAAB-ESP).